Hubungan antara Perilaku Cybersex dengan Sleep Quality pada Pengguna Twitter - Diah Puspitasari; Lilim Halimah (UNISBA Press, 2023)
Abstract. The global era has made the internet a primary necessity for its users, including the need for social media usage. Inappropriate use of Twitter social media can have negative effects such as cybersex behavior. For those who continuously engage in cybersex and constantly think about pornographic content, it impacts sleep quality. This study aims to determine the relationship between cybersex behavior and sleep quality among Twitter users. The study utilizes a correlational method with 97 respondents. Sleep quality is measured using the Pittsburgh Sleep Quality Index (PSQI) developed by Buysee et al. (1989). Internet Sex Screening is used to measure cybersex behavior. Data analysis technique employs the Spearman rank correlation. The research findings show a correlation coefficient of r = -0.648 with a p-value of 0.000 < 0.05. This means that there is a significant negative relationship between cybersex behavior and sleep quality among Twitter users. Abstrak. Era global menjadikan internet sebagai kebutuhan utama bagi para penggunanya, termasuk pada kebutuhan akan penggunaan media sosial. Penggunaan media sosial twitter yang tidak tepat dapat menimbulkan dampak negatif seperti perilaku cybersex. Bagi mereka yang Mengakses cybersex secara terus menerus dan selalu memikirkan konten – konten pornografi berdampak pada kualitas tidur. Penelitian ini bertujuan untuk mengetahui hubungan antara perilaku cybersex dan sleep quality pada pengguna Twitter. Penelitian ini menggunakan metode korelasional dengan responden sebanyak 97 orang. Kualitas tidur diukur menggunakan Pittsburgh Sleep Quality Index (PSQI) yang disusun oleh Buysee et al. (1989). Internet Sex Screening digunakan untuk mengukur perilaku cybersex. Teknik analisis data menggunakan korelasi rank spearman. Hasil penelitian menunjukkan nilai r= -0.648 dengan nilai p = 0.000 <0.05. Artinya Terdapat hubungan negatif yang signifikan antara perilaku cybersex dengan sleep quality pada pengguna Twitter.